Influence of selenium on oxidative stress in athletes - Sieja, K.; Mach-Szczypinska, J.; Kois, N.; Ler, P.; Piechanowska, K.; Stolarska, M. (Central European Journal of Sport Sciences and Medicine, 2016)
The aim of the study was to analyze the influence of selenium (Se) on the course of oxidative stress in trained athletes, on the basis of own former published studies and the reference of literature. In a number of references it was shown that the application of Se led to the diminishing of oxidative stress during the physical exercises in athletes. The application of Se to athletes - led to the increase of peroxidase glutathione the main selen - dependent enzyme. The fact of increased concentration of malondialdehyde (MDA) in blood serum, the main metabolite of lipid peroxidation can indirectly evidence about the intensity of physical endurance. This increase is significantly smaller in individuals taking exogenous antioxidative diet supplement containing Se. Moreover there is the evidence that oxidative muscles damage during physical effort could be diminished by compounds with antioxidative properties. Taking into consideration, the obtained results by many of authors empower to the conclusion that application of Se diminishes the degree of peroxidation of lipids in trained athletes.